IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBENTUKAN NILAI SOSIAL DI SEKOLAH DASAR - Ika Yatri; Muhammad Azhar Nawawi; Bella Firdha Novia Widayanti; Camilia Habibah; Muhammad Farras Qoid Mufadhol; Najma Kamila Putri Syarief; Salwa Az Zahrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education in elementary schools is very important in shaping children's personalities from an early age. At this stage, children experience rapid cognitive and emotional development, so that instilling moral values ​​such as honesty, responsibility, and empathy become the main foundation for forming individuals with integrity. Implementation of character education can be done with various approaches: integration of values ​​in the curriculum, extracurricular activities, project-based learning, role models from teachers, and collaboration with parents and the community. Effective character education contributes to positive student behavior, good emotional management, and increased academic achievement. Thus, character education not only forms students who are intellectually intelligent, but also have noble morals.Keywords: Character Education, Moral Values, Honesty, Responsibility, Empathy.